Representasi Kebudayaan Jawa dalam Novel Garwa Karya Cheris Ivana: Studi Antropologi Sastra - Jeni Dwi Astrit; Onok Yayang Pamungkas; Eko Sri Israhayu; Akhmad Fauzan; Mulasih Mulasih (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2026)
Research focused on literary texts within the cultural context of their origin is known as literary anthropology Studies utilizing this approach are essential for contributing to the preservation of Indonesian culture. This research aims to identify the elements of Javanese culture represented in Cheris Ivanas novel, Garwa, and to examine the influence of Javanese culture on the authors creative process. This study employs a qualitative approach with a hermeneutic method. Data collection was conducted through Interviews, close reading, and note-taking techniques. The data analysis follows the Miles and Huberman interactive model, which consists of three stages: (1) data reduction, (2) data display, and (3) conclusion drawing and verification. The findings indicate that Garwa incorporates various elements of Javanese culture woven into its narrative structure. These cultural elements encompass linguistic aspects, religious systems, artistic expressions, social organizations, and technological or material life systems. Furthermore, Cheris Ivanas creative process in writing Garwa was influenced by several Javanese cultural factors, including her own ancestral roots in the Surakarta Javanese community, her admiration for Gusti Bhre, her affection for Pura Mangkunegaran, and her extensive reading of literature regarding Javanese traditions